2008
DOI: 10.1291/hypres.31.1115
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Home and Office Blood Pressures among Treated Hypertensive Patients from the Japan Home versus Office Blood Pressure Measurement Evaluation (J-HOME) Study

Abstract: , the J-HOME Study Group* This study sought to clarify the factors associated with the magnitude of the difference between home and office blood pressures in treated hypertensive patients. Study subjects consisted of 3,308 essential hypertensive patients (mean age, 66 years; males, 44%) receiving antihypertensive treatment in primary care settings in Japan. Patients were classified into 3 groups (the home effect group, small difference group, and office effect group) according to tertiles of the magnitude of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, the results of the J-HOME study showed that the difference between CSBP and MHSBP is increased in older patients. 25 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results of the J-HOME study showed that the difference between CSBP and MHSBP is increased in older patients. 25 …”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Masked hypertension is prevalent in CKD patients, 13,14 and older age is associated with a greater prevalence of masked hypertension among treated hypertensive patients. 15,16 Thus, HBP measurement might contribute to improved BP control in elderly CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Educational factor, e.g., years of schooling and academic degrees attained, were proven by Liu et al and Sun et al to be inversely associated with BP [32,33], most likely related to personal awareness and healthy lifestyle [34]. Diabetes and insulin resistance, through means of recently uncovered mech- [40,41].…”
Section: Discussionmentioning
confidence: 99%